The Relationship of Exclusive Breastfeeding with Stunting Incidents in Toddler Ages (1 -5 Years) in Sampiran Village, Talun District, Cirebon Regency - Marwati Marwati; Ruswati Ruswati; Sofiyati Sofiyati; Yani Trihandayani; Titin Supriatin (Journal of Social Research, 2023)
In 2022, the Cirebon District faced a persistent issue of high stunting rates, affecting 15,299 cases or approximately 9.4% of its population. This study focuses on Sampiran Village, Talun Subdistrict, within the Cirebon District, aiming to investigate the correlation between exclusive breastfeeding and stunting in toddlers. Employing a cross-sectional study design with purposive sampling, data collection included questionnaires and anthropometric measurements provided by parents of the participating toddlers. Results revealed that 63.2% of toddlers did not receive exclusive breastfeeding, and 21% of them experienced stunting. Statistical analysis demonstrated a significant relationship between exclusive breastfeeding and stunting occurrence (p < 0.05), with an Odds Ratio of 1.133. This suggests that exclusive breastfeeding can reduce the risk of stunting by 1.133 times, emphasizing its crucial role in stunting prevention among toddlers. These findings underscore the urgency of promoting and educating parents and caregivers about the benefits of exclusive breastfeeding. Encouraging exclusive breastfeeding practices can potentially mitigate the prevalence of stunting in this vulnerable age group within the Cirebon District, ultimately contributing to better child health and well-being.